Recurrent Hemoptysis in Patient with Primary Pulmonary Hypertension – A Case Report and Literature Review - Indra Widya Nugraha; Bambang Irawan; Lucia Kris Dinarti (ACI (Acta Cardiologia Indonesiana), 2017)
Pulmonary hypertension (PH) is defned as an increase in mean pulmonary arterial pressure (mPAP) ≥ 25 mmHg at rest as assessed by right heart catheterization (RHC). The symptoms of PH are non-specifc and mainly related to progressive right ventricular (RV) dysfunction. In some patients the clinical presentation may be related to mechanical complications of PH andthe abnormal distribution of blood ﬂow in the pulmonary vascular bed, include hemoptysis related to rupture of hypertrophied bronchial arteries. Hemoptysis is a serious complication that is rarely reported in patients with pulmonary arterial hypertension (PAH). Hemoptysis severity ranges from mild to very severe leading tosudden death. Hemoptysis are reported to be a terminal stage ofa complication due to PAH with prevalence is variable, from 1% to 6%. Although the incidence is quite rare, the presence of recurrent hemoptysis in patients with pulmonary hypertension is a sign of poor prognosis. Bronchial artery embolization is suggested as an acute emergency procedure in the case of severe hemoptysis or as elective intervention in cases of frequent mild or moderate episodes.